Ideal-typical Competence Profile of Industrial Buyer-Seller Relationship Controllers in Technology Firms –Empirical Evidence from Austria - Markus Zunk, Bernd (International Journal of Industrial Engineering and Management, 2013)
Customer relationship managers in dynamic technology markets are not able to control industrial buyer-seller relationships both efficiently and effectively without support for two reasons. First, the characteristics of industrial goods and services are becoming more and more complex. Second, the organizational structure of the procurement process intechnology firms causesa diversity ofmanagementtasks. This requires manifold competencies of controllers supporting the relationship managers. The aim of this paper is to widen the traditional internal business view of controllersby incorporating an external perspectiveand introducinga theoretical competence model for industrial buyer-seller relationship controllers. To test thismodel,data from a large-scale survey with 251 respondents from the Austriantechnology sector was used. This paper providesthe first empirically backed ideal-typical competence profile for buyer-sellerrelationship controllers. The findings enable human resource managers intechnology firmsto recruit the most suitable personand to choose adequate qualification programs. Article history: Received (11November 2012); Revised (15May 2013); Accepted (27 May2013)